OPTIMIZATION OF CROPPING PATTERN TO INCREASE THE BENEFIT OF AGRICULTURE OUTCOME USING LINEAR PROGRAMMING AND CONVENTIONAL METHOD (Case Study Cirasea Irrigation Scheme of Bandung Regency West Java Province) - Respaty Yuliantara - NIM : 95014304 , Bangbang
The area of Cirasea irrigation scheme Is 2470 Ha. It is technical irrigation network located in Bandung Regency. Cirasea irrigation scheme often experiences shortage of water. The cropping pattern applied to the regulation of Water Resources Agency West Java Province in 2014/2015 was rice plant/Rice plant-Crops Plants/ crops Plant scane with cultivation process beginning in October I, but due to water shortage, The planned cropping pattern wasnot applied in 2014/2015 To meet the amount of water needed in Cirasea irrigation scheme, optimization of The existing available Water, Water optimization is carried out. with the aim Optimization to have appropriate cropping patterns and to increase benefit of agriculture out come to the maximum. Optimization was done by using linear programming through a mathematical model solved by using the simplex method and Conventional method. The scenario of Cropping pattern optimization consists of (two) 2 scenarios, namely: (1) The planting begins in October I, (2) The planting begins in November I. and (3) With Conventional Method, in each Linear Programing scenario simulated with (Three) 3alternatives, the first alternative is full of rice and crops in the planting for one year, the second alternative All Irigation Scheme is Planted Rice in MT 1, Rice and crops planted in MT 2 and All off the Irigation Scheme just Planting with Rice in MT 3. Based on the Wide Area optimization The Largest Optimation Result Is The Second Scenario and Third Alternative, the beginning of planting in November I, amounted to 142%. With cropping pattern of optimization result in The Second scenario, the biggest advantage in The Second Scenario and The Third alternative is Rp 85.641.567.132,00, and lower Profit Is In the First Alternative Is Rp.76.780.944.253,00. The Second Scenario and The Third alternative, the largest profit in one year from the Rice plant is Rp 65.641.567.132,00. The best choice falls to The Second Scenario and The Third Alternative . However, if we compare between Linear method and conventional Method, Conventional Method is more profitable with the benefit Value Rp. 188.480.551.500,00.